Collaborative Synergy between Islamic Education Teachers and School Counselors in Fostering Religious Character and Responsibility - Auliya, Muhamad Fahmi Ridho; Sutomo, Imam; Sriyanti, Lilik (Institut Agama Islam Sunan Giri (INSURI) Ponorogo, 2026)
This study investigates the collaborative synergy models between Islamic Religious Education (PAI) teachers and School Counselors (BK), designed to strengthen religious character and responsibility among students in Magelang City, Indonesia. Addressing the critical limitations of siloed character education amidst rising urban moral challenges, such as juvenile delinquency, this research argues that isolated interventions fail to address the holistic needs of students. Employing a Qualitative Case Study design, the research was conducted across five public junior high schools (SMP Negeri 1, 2, 3, 5, and 13) in Magelang City. Data were rigorously gathered using three fundamental techniques: (1) in-depth semi-structured interviews with 15 key informants to explore collaborative experiences and role divisions; (2) participant observation of daily religious habituations and counseling sessions; and (3) documentation analysis of guidance programs and student records to triangulate the findings. The findings reveal a comprehensive collaborative framework categorized into five operational models: (1) Preventive, utilizing habituation routines like GLISUCI (Scripture Literacy) and 5S; (2) Curative, applying psycho-theological counseling for behavioral restoration; (3) Thematic-Integrative, involving curriculum infusion; (4) Extracurricular, fostering experiential learning in Scouts and ROHIS (Islamic Spirituality); and (5) Consultative-Collaborative, focusing on parental engagement. The study demonstrates that this synergy effectively integrates theological norms (Aqidah) with psychological guidance, transforming student behavior from mere compliance into intrinsic responsibility. Despite identifying structural rigidities and epistemological gaps between the professions as persistent barriers, the study concludes that formalizing this collaboration through explicit institutional policy is critical. Such institutionalization is necessary to establish a unified, holistic character-building ecosystem capable of navigating the complexities of modern urban educational environments.